2019
DOI: 10.1111/apm.12922
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitution mutations and mRNA expression levels of the pbp5 gene in clinical Enterococcus faecium isolates conferring high level ampicillin resistance

Abstract: Darehkordi H, Saffari F, Mollaei HR, Ahmadrajabi R. Amino acid substitution mutations and mRNA expression levels of the pbp5 gene in clinical Enterococcus faecium isolates conferring high level ampicillin resistance. APMIS 2019; 127: 115-122.In this study, clinical ampicillin-resistant Enterococcus faecium isolates with minimum inhibitory concentrations (MICs) for ampicillin in the ranges from 128 to ˃512 lg/mL (n = 17) and two ampicillin-susceptible isolates (MIC 1 lg/mL) were investigated. No b-lactamase pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…All 24 genomes analyzed had several mutations in the pbp5 gene ( Table S3 ) that have been associated with pbp5 clade A1R, which mostly comprises ampicillin-resistant isolates [ 21 ]. Even though most data seem to indicate that there are no consistent amino acid changes correlating with specific increases in the MICs of ampicillin [ 33 ], a recent study by Darehkordi et al established a link between high ampicillin MICs, high PBP5 expression levels, and specific pbp5 mutations [ 34 ]. A comparison between pbp5 -containing platforms (associated with AmpR) of our sequenced genomes with a large transferable pbp5 -containing platform that we have previously described in a clinical isolate [ 21 ] allowed the partial identification of highly similar genetic platforms carrying different metabolic and adaptive features, including virulence genes (e.g., sgrA or fms2 important in biofilm formation) in AmpR- Efm of different origins ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…All 24 genomes analyzed had several mutations in the pbp5 gene ( Table S3 ) that have been associated with pbp5 clade A1R, which mostly comprises ampicillin-resistant isolates [ 21 ]. Even though most data seem to indicate that there are no consistent amino acid changes correlating with specific increases in the MICs of ampicillin [ 33 ], a recent study by Darehkordi et al established a link between high ampicillin MICs, high PBP5 expression levels, and specific pbp5 mutations [ 34 ]. A comparison between pbp5 -containing platforms (associated with AmpR) of our sequenced genomes with a large transferable pbp5 -containing platform that we have previously described in a clinical isolate [ 21 ] allowed the partial identification of highly similar genetic platforms carrying different metabolic and adaptive features, including virulence genes (e.g., sgrA or fms2 important in biofilm formation) in AmpR- Efm of different origins ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Enterococcus faecium showing ampicillin resistance is an additional problem in the clinical chemotherapy of enterococci [ 36 ]. Chromosomal point mutations putatively conferring resistance to linezolid (in 23S rRNA and ribosomal proteins L3/L4/L22) were not detected in our isolates.…”
Section: Discussionmentioning
confidence: 99%
“…A higher resistance to these antibiotics is usually associated with a higher expression of PBP5 proteins [ 113 , 114 ] or to mutations in the amino acid gene sequence that lead to alterations of this protein’s molecular structure [ 114 , 115 , 116 ]. When evaluating the relation between pbp5 sequences of E. faecium and penicillin’s minimal inhibition concentration (MIC) presented by these isolates, a study by Galloway-Peña et al [ 115 ], corroborated later by another study by Pietta et al [ 116 ], concluded that isolates that presented a MIC ≤ 2 µg/mL and isolates that presented a MIC ≥ 16 µg/mL had a 5% difference in the pbp5 sequence, which remounted to the presence of two distinct allelic forms: a more susceptible (PBP5-S) and a more resistant (PBP5-R) form.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…However, both studies concluded that the determination of which amino acid changes were responsible for this decrease in susceptibility to β-lactams was difficult. The divergence seen in results described in other studies also reinforces this conclusion, although some changes such as an additional serine after amino acid position 466 (Ser-466) or amino acid substitutions (for instance the substitution of a methionine, Met-485, for an alanine or threonine (Met-485 → Ala/Thr), the substitution of a glutamic acid, Glu-629, for a valine, and also the substitution of an aspartic acid, Asp-496, for a lysine) have been more frequently associated to a high-level of penicillin resistance than others [ 114 , 115 , 117 , 118 , 119 ]. Although it has been proven that this PBP is responsible for some degree of resistance to penicillins, high-level resistance cannot be solely justified by the increased expression or mutations of the pbp5 gene, which means that other factors should also play some kind of role in this adaptation [ 106 , 114 ].…”
Section: Antibiotic Resistancementioning
confidence: 99%